Pengaruh Kepemimpinan, Motivasi dan Kinerja Pegawai Terhadap Kepuasan Kerja pada Kantor Kecamatan Ngantru Kabupaten Tulungagung - Sulistiono, Sulistiono; Santyo Rusandy, Deby (Otonomi, 2024)
The purpose of this research is to know and analyze the influence of leadership, the motivations and performance of employees to the satisfaction of employment at the district office Ngantru Tulungagung regency .This research uses descriptive quantitative methods. The population and samples of all office employees, there were 22 responders. Data insertion method using questionnaire, field observation and literature method. While data analysis uses linear regression analysis. The research shows that leadership, The staff's motivations and performance have an effect on employees' satisfaction. It is supported by the result of r square or coefficient determination (KD) shows 90.6 % so interpreted if variable X1 (leader), X2 (motive) and X3 (employee performance) have a contribution of 90.6 % to variable Y (job satisfaction) and 9.4 % are influenced by other factors besides variable X. In addition, in the f count 68,347 receive is worth of 0,000 sig. Thus showing that the f count > f table or 68,347 > 3,13 with the sig 0,000 < 0,05. Thus received hypothesis. While on the outcome of the t count for partial that leadership, motivation and the employee performance led to satisfaction of employees at the district office Ngantru Tulungagung regency